Quick detection of Carassius auratus herpesvirus (CaHV) by recombinase-aid amplification lateral flow dipstick (RAA-LFD) method - Gui, Lang; Zhao, Yun; Xu, Dan; Li, Xinyu; Luo, Jianhua; Zhou, Wenzong; Li, Mingyou (Frontiers in Cellular and Infection Microbiology, 2022)
Crucian carp (Carassius auratus) is one of the major freshwater species and is also a common food fish in China. Recently, Carassius auratus herpesvirus (CaHV) could induce fatal viral disease with high mortality of crucian carp, which had caused huge economic losses. In this study, we described a rapid and simple recombinase-aid amplification (RAA) assay coupled with lateral flow dipstick (LFD), which could achieve sensitive diagnosis of tumor necrosis factor receptor (TNFR) of CaHV within 35 min at 40°C. Our RAA-LFD method had a satisfactory detection limit of 100 gene copies per reaction, which was 100-fold more sensitive than traditional PCR. In addition, no cross-reaction was observed with other viral pathogens, including koi herpesvirus (KHV), cyprinid herpesvirus 2 (CyHV-2), infectious hematopoietic necrosis virus (IHNV), spring viremia of carp virus (SVCV) and grass carp reovirus (GCRV). Furthermore, the overall cost of the method was cut in half compared to previous studies. In conclusion, RAA-LFD assay is therefore, a promising alternative for point-of-care testing (POCT) of CaHV, which is feasible and of certain value in application of aquatic disease control.